2012
DOI: 10.1111/j.1365-2427.2012.02763.x
|View full text |Cite
|
Sign up to set email alerts
|

Range of variability of channel complexity in urban, restored and forested reference streams

Abstract: Summary 1. Channel complexity is an important ecological property of stream systems and is often targeted for restoration in channelised urban streams. However, channel complexity is rarely defined explicitly, and little research on channel complexity has been conducted in streams in urban catchments that have not been directly channelised by human activities. Therefore, it remains unclear whether restoration of non‐channelised urban streams has improved complexity. 2. We explicitly define channel complexity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 100 publications
(179 reference statements)
1
29
0
Order By: Relevance
“…This issue is further complicated by the absence of clear, agreed-upon, definitions of how to define and measure habitat heterogeneiity. The importance of quantitatively and precisely assessing habitat heterogeneity was demonstrated by Laub et al [49] who found that many unrestored (but non-channelized) urban streams had relatively high heterogeneity (measured through several specific metrics including variability in width, depth, velocity, thalweg profile, and bed sediment sorting) when compared to reference, forested sites, and that "restored" sites were often not more complex than unrestored sites. Thus, there is no a priori reason to assume that "heterogeneity enhanced" sites have more heterogeneity than unrestored urban stream sites.…”
Section: Habitat Metricsmentioning
confidence: 99%
“…This issue is further complicated by the absence of clear, agreed-upon, definitions of how to define and measure habitat heterogeneiity. The importance of quantitatively and precisely assessing habitat heterogeneity was demonstrated by Laub et al [49] who found that many unrestored (but non-channelized) urban streams had relatively high heterogeneity (measured through several specific metrics including variability in width, depth, velocity, thalweg profile, and bed sediment sorting) when compared to reference, forested sites, and that "restored" sites were often not more complex than unrestored sites. Thus, there is no a priori reason to assume that "heterogeneity enhanced" sites have more heterogeneity than unrestored urban stream sites.…”
Section: Habitat Metricsmentioning
confidence: 99%
“…We therefore picked sinuosity (S) as our metric of planform complexity. By contrast, many metrics that capture some aspect of vertical complexity of the thalweg have been proposed (Laub et al, 2012). The most common metric is the density/spacing of instream geomorphic features, yet this metric does not incorporate information on the vertical height of bed deviations.…”
Section: Hyporheic Potential Versus Hyporheic Exchangementioning
confidence: 97%
“…For example, the spatial variability of shallow sediment hydraulic conductivity (K) has been measured within one or two streams (e.g., Ryan and Packman, 2006;Ryan and Boufadel, 2007;and Kennedy et al, 2009a,b). Similarly, Laub et al (2012) examined how restoration in urban areas affects channel ''complexity,'' which is defined in many ways but includes variations in streambed topography that drive hydraulic head gradients that drive bidirectional exchange. The relationship between hyporheic potential and hyporheic exchange is discussed further in ''Hyporheic Potential Versus Hyporheic Exchange,'' below.…”
Section: Introductionmentioning
confidence: 99%
“…1; Choi 2007, Violin et al 2011, Laub et al 2012, Hawley et al 2013. Streams in urban landscapes often have irreversibly altered physical characteristics at small-to-broad spatial scales that prevent a return to natural hydrogeomorphic characteristics of reference conditions (e.g., unattainable channel slopes because of permanently altered local topographies; Wohl et al 2005).…”
Section: Reference-condition Approachmentioning
confidence: 99%
“…From an ecological perspective, consistently effective strategies for restoring streams in urban catchments are elusive , Violin et al 2011, Laub et al 2012). The primary ecological barriers for restoring streams in modified landscapes is the extent to which drivers of stream condition (e.g., flow, sediment supply, water quality, habitat availability, etc.)…”
mentioning
confidence: 99%